2015
DOI: 10.15288/jsad.2015.76.781
|View full text |Cite
|
Sign up to set email alerts
|

Coping Expectancies, Not Enhancement Expectancies, Mediate Trauma Experience Effects on Problem Alcohol Use: A Prospective Study From Early Childhood to Adolescence

Abstract: ABSTRACT. Objective:The relationship between experiencing trauma and increased alcohol consumption has been well established. Exposure to childhood trauma has been linked to both early onset of drinking and problematic substance use. However, the mechanisms underlying this relationship remain unclear. The results of early work suggested that drinking to relieve negative affect (i.e., drinking to cope) was driving this connection. However, the findings of more recent work suggest that drinking might be used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 47 publications
1
38
0
2
Order By: Relevance
“…Additionally, adolescents’ exposure to fathers’ alcohol use was associated with coping AE, indicating that when adolescents see their fathers drinking more often, they associate alcohol use with drinking to forget problems. This is important, since coping AE are found to be predictive of peak alcohol use in later adolescence (Jester et al., ). Fathers’ exposure appeared predictive of enhancement AE among boys.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, adolescents’ exposure to fathers’ alcohol use was associated with coping AE, indicating that when adolescents see their fathers drinking more often, they associate alcohol use with drinking to forget problems. This is important, since coping AE are found to be predictive of peak alcohol use in later adolescence (Jester et al., ). Fathers’ exposure appeared predictive of enhancement AE among boys.…”
Section: Discussionmentioning
confidence: 99%
“…However, aggression did not mediate the association between emotional neglect and non-violent delinquency, as well as between physical neglect and violent delinquency (58). Jester et al (48) showed that high alcohol coping expectancy, i.e., consuming alcohol to handle stress, mediates the association between inter-parent violence and both peak alcohol use and heavy episodic drinking (when taking distress as intermediate predictor into account). In contrast, no mediation effects were found for alcohol enhancement expectancy, i.e., consuming alcohol to improve mood (48).…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Esta exposición puede ocurrir de manera directa, en forma de victimización; o indirectamente, al presenciar algún tipo de violencia (Foster y Brooks-Gunn, 2009). La exposición a la violencia en la infancia resulta en índices más altos de desórdenes por estrés postraumático, depresión y problemas conductuales (Jester, Steinberg, Heitzeg y Zucker, 2015). Además, es un factor de riesgo para el desarrollo de abuso de sustancias en la adultez (Odds Ratio (OR) 2,84, IC 95% [1,26]) (Benjet et al, 2010;Jester et al, 2015;Kuhar, 2012).…”
unclassified
“…La exposición a la violencia en la infancia resulta en índices más altos de desórdenes por estrés postraumático, depresión y problemas conductuales (Jester, Steinberg, Heitzeg y Zucker, 2015). Además, es un factor de riesgo para el desarrollo de abuso de sustancias en la adultez (Odds Ratio (OR) 2,84, IC 95% [1,26]) (Benjet et al, 2010;Jester et al, 2015;Kuhar, 2012). De manera similar, el abuso sexual grave durante la infancia, se ha relacionado con un aumento en el riesgo para el abuso/dependencia al alcohol (OR 3,3, IC 95% [1,7-6,6]), o el abuso/dependencia a otras drogas (OR 5,1, IC 95% [2,5-10,2]) en la edad adulta temprana .…”
unclassified